ANALISIS PERBANDINGAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH PEMILU SERTA PELANTIKAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 PADA PERUSAHAAN IDX30 - Putra Triyansyah; Sulastri Sulastri; Deby Handayani (Ensiklopedia of Journal, 2026)
This study aims to determine whether there is a difference in abnormal returns and trading volume activity before and after the presidential and vice presidential elections this study also aims to the inauguration of the president and vice president in 2024. This type of research uses a quantitative approach with a comparative type and the population in this study were stocks that were consistently listed in the IDX30 index, namely 30 companies during the study period. The data analysis technique used in this study was a parametric test, namely the Paired Sample T-test. The calculation results show that 1) there is no difference in the average abnormal return before and after the 2024 presidential and vice presidential elections. 2) there is no difference in the average trading volume activity before and after the 2024 presidential and vice presidential elections. 3) there is no difference in the average abnormal return before and after the inauguration of the president and vice president in 2024. 4) there is no difference in the average trading volume activity before and after the inauguration of the president and vice president in 2024. Which means that investors do not respond to the events of the general election and the inauguration of the president and vice president in 2024.Keywords : Abnormal Return, Trading Volume Activity, president and vice president elections in 2024, inauguration of the president and vice president in 2024